Dynamic self-assembly and self-organized transport of magnetic micro-swimmers. Issue 1 (December 2017) - Kokot, Gašper; Kolmakov, German; Aranson, Igor; Snezhko, Alexey
Abstract We demonstrate experimentally and in computer simulations that magnetic microfloaters can self-organize into various functional structures while energized by an external alternating (ac) magnetic field. The structures exhibit self-propelled motion and an ability to carry a cargo along a pre-defined path. The morphology of the self-assembled swimmers is controlled by the frequency and amplitude of the magnetic field.